Trade union investment schemes: a blemish on the social movement unionism outlook of South African unions? - Rubushe, Melikaya (Rhodes University, Faculty of Humanities, Department of Sociology, 2010)
South African trade unions affiliated to Congress of South African Trade Unions (COSATU) have taken advantage of the arrival of democracy and newly found opportunities available through Black Economic Empowerment to venture into the world of business by setting up their own investment companies. The declared desire behind these ventures was to break the stranglehold of white capital on the economy and to extend participation in the economic activities of the country to previously disadvantaged communities. Using the National Union of Mineworkers and the Mineworkers' Investment Company as case studies, this dissertation seeks to determine whether unions affiliated to the Congress of South African Trade Unions (COSATU) are advancing the struggle for socialism through their investment schemes. Secondly, the dissertation determines whether, in the activities of the schemes, internal democracy is preserved and strengthened. The theoretical framework of this dissertation emerges from arguments advanced by Lenin and Gramsci on the limitations of trade unions in terms of their role in the struggle against capitalism. In addition, the argument draws on the assertions by Michels regarding the proneness of trade union leadership to adopt oligarchic tendencies in their approach to leadership. Of interest is how, according to Gramsci, trade unions are prone to accepting concessions from the capitalist system that renders them ameliorative rather than transformative. Drawing from Michels' 'iron law of oligarchy', the thesis examines whether there is space for ordinary members of the unions to express views on the working of the union investment companies. By looking at the extent to which the investment initiatives of the companies mirror the preferences of the ordinary members of the unions, one can determine the level of disjuncture between the two. The study relies on data collected through interviews and documentary material. Interviews provide first-hand knowledge of how respondents experience the impact of the investment schemes. This provides a balanced analysis given that documents reflect policy stances whereas interviews provide data on whether these have the stated impact. What the study shows is a clear absence of space for ordinary members to directly influence the workings of union investment companies. It is also established that, in their current form, the schemes operate more as a perpetuation of the capitalist logic than offering an alternative system.
Keywords: Labor unions -- South Africa; Labor unions and communism; Cosatu; Economic development -- South Africa; National Union of Mineworkers (South Africa); Labor unions -- Finance; Business enterprises, Black -- South Africa; Investments -- South Africa